Not Begetting the Future: Technological Autochthony, Sexual Reproduction, and the Mythic Structure of The Matrix. - Kimball, A. Samuel (Journal of Popular Culture (Wiley-Blackwell))
The article presents information about the motion picture "The Matrix." The movie, however, is ambivalent about its mythic elements, for it simultaneously affirms and denies its autochthonous motifs. In particular, the movie's storyline violently resists the myth of autochthony while the film's imagery and techniques recreate the myth's fundamental predication. The result is a powerful tension that discloses the strange "logic" of autochthony, the way this concept denies the reproductive context of human existence in order to "conceive" another kind of advent and destiny for humankind. The storyline of "The Matrix" would seem to, attest to the superiority of the human to the machine, consciousness to artificial intelligence, knowledge to illusion, experience-above all the transformative experience of love-to the ersatz forms of computer generated virtual experiences, and so on. The film's protagonist is, by day, an unassuming computer programmer, Thomas Anderson played by Keanu Reeves-single, white, and indifferent about his job. He is, by night, the notorious hacker, known as Neo, who eventually meets up with the revolutionary leader Morpheus played by Laurence Fishburne. Under the tutelage of this man, the spiritual source of his final triumph, Neo saves the world from the dominion of an omnipresent Al. The movie's plot thus enacts a variation of the myth of the hero.